The Importance of Epidemiological Study in the Diagnosis of Human Intestinal Miasis: A Case Study - Zulbey Rivero de Rodríguez; Iris Díaz Anciani; Rafael Villalobos (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2007)
The word "miasis" defines the infestation of humans by the larvae of dipteros (flies). The case of a boy is described who noted on two occasions, the expulsion of larvae with a characteristic mouse tail, compatible with Eristalis tenax. The observed clinical manifestations in the patient led to the diagnosis of intestinal miasis from this fly. The epidemiological survey conducted on the family and the review of other environmental factors that could affect the presence of these larvae in the toilet water, permitted researchers to discard the initial diagnosis. Performing other laboratory examinations was another determining factor in being able to carry out a correct diagnosis of the clinical picture present. An exhaustive determination of diverse epidemiological parameters is recommended before concluding the diagnosis of intestinal miasis by E. tenax.